Determinants of female labor force participation: implications for policy in Qatar - Noora Lari (14158824) (2022)
The aim of this study was to examine the microlevel factors affecting women’s participation in the Qatar workforce, as the gender gap in employment is still wide, and addressing this issue remains an essential item on the government’s policy agenda. Data were collected via a national telephonic survey of a representative sample of Qatari nationals, chosen using simple random sampling. A regression analysis was performed with women’s employment, individual-level characteristics (e.g., age, education, and marital status), and household-level factors (e.g., number of children below 18 years of age and household monthly income) as the variables. The analytical model highlighted the microlevel predictors at the individual level as well as the public attitudes toward societal obstacles that have adverse effects on female labor force participation. The results revealed several indicators that affect women’s participation in the labor force, including education level, marital status, and age. These constructs were found to have the strongest (direct or indirect) effects in terms of pushing Qatari women into the labor market. The originality of this study lies in its ability to explain how state-directed initiatives can encourage women to participate in the labor market and thus facilitate a rapid increase in the number of employed women in Qatar. A methodological limitation of the cross-sectional survey design used in this study is that it limits the causations between the government interventions and the research outcomes. The findings indicate the need for further improvement in welfare regimes at the intrastate level. Other Information Published in: Cogent Social Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311886.2022.2130223